Are PDF documents accessible? - Turró MR (Information Technology & Libraries, 2008)
Adobe PDF is one of the most widely used formats in scientific communications and in administrative documents. In its latest versions it has incorporated structural tags and improvements that increase its level of accessibility. This article reviews the concept of accessibility in the reading of digital documents and evaluates the accessibility of PDF according to the most widely established standards.